Bio-inspired micro/nanomotor with visible light dependent in situ rotation and phototaxis. (December 2022) - Wang, Dalei; Jiang, Jiwei; Hao, Bo; Li, Mingtong; Chen, Zongchen; Zhang, Hui; Wang, Xin; Dong, Bin
Highlight: Realized a biomimetic visible light-driven micro/nanomotor (MNM) with both the rotational motion and the negative phototactic motion behavior. The MNM exhibited the switchable motion behavior when the irradiation condition changes. The MNM exhibited the controlled in situ clockwise/counterclockwise rotation with designated angles. Abstract: In nature, many microorganisms (such as volvox) normally rotate in situ and exhibit the phototactic motion when they sense the changes of the light signal. However, it is still challenging for the artificial micro/nanomotor counterpart to achieve such switchable motion behavior. Herein, we report a biomimetic visible light driven micro/nanomotor (MNM) with motion behavior similar to that of the volvox. The MNM, which consists of Ag nanoparticle decorated WO3 microrod (with a size of ∼5 μm), exhibits the in-situ rotation with an angular speed of ∼ 4.67 rad/s (under vertical light irradiation with an intensity of 600 mW/cm 2 ) and shows the negative phototaxis when the irradiation condition is changed to the tilted one (e.g. 45° incident angle) with the angular and linear velocities of ∼ 4.59 rad/s and ∼ 1.47 μm/s, respectively. The biomimetic motion behavior relies on the interaction between the two underlying mechanisms, i.e. self-electrophoresis and self-diffusiophoresis. More interestingly, the MNM exhibits the controlled in situ clockwise/counterclockwise rotation with designated angles (e.g. 90°, 180°). The results in the current study may further boost the development of light-driven MNMs with biomimetic features for a wide range of microfluidics, microrobotics, and cargo transportation applications. Graphical abstract: Image, graphical abstract